2006
DOI: 10.1007/s11065-006-9012-8
|View full text |Cite
|
Sign up to set email alerts
|

Group Intervention Studies in the Cognitive Rehabilitation of Individuals with Traumatic Brain Injury: Challenges Faced by Researchers

Abstract: There are many factors to consider in designing and interpreting group studies. These include both analytic considerations, such as the selection of valid and reliable outcome measures, and subjective considerations, such as the selection of outcomes that are perceived to be important to participants and researchers. In this paper, we review key issues to consider in the design of group studies in neurorehabilitation, using problem-solving studies in traumatic brain injury as an example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
1
19
0
2
Order By: Relevance
“…(f) Evidence-based medicine is rooted in the belief that the strongest evidence is based on RCTs, which control for biases better than other methodologies. Nevertheless, Kennedy and Turkstra (2006) noted that even though the RCT framework has been adopted by behavioral therapists it was originally designed for clinical drug trials, many features of which are not appropriate, practical, or relevant in behavioral intervention research. Moreover, RCTs were initially designed to measure change by using a restricted number of primary outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(f) Evidence-based medicine is rooted in the belief that the strongest evidence is based on RCTs, which control for biases better than other methodologies. Nevertheless, Kennedy and Turkstra (2006) noted that even though the RCT framework has been adopted by behavioral therapists it was originally designed for clinical drug trials, many features of which are not appropriate, practical, or relevant in behavioral intervention research. Moreover, RCTs were initially designed to measure change by using a restricted number of primary outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RCTs were initially designed to measure change by using a restricted number of primary outcome measures. Thus, due to the wide individual variability among clinical features following an ABI (with the consequent need to include multiple outcome measures) Kennedy and Turkstra (2006) concluded that a singlecase rather than an RCT approach might be useful to gather evidence for effective interventions. In fact, behavioral treatments applied during individually tailored interventions should provide the best available advice, especially in an inpatient/residential rehabilitation environment.…”
Section: Discussionmentioning
confidence: 99%
“…In order for this to best happen, future research needs to carefully consider choices regarding the use of control groups, measurement strategies, and treatment modalities (Kennedy and Turkstra 2006). In the area of addiction treatment, additional questions include how cognitive rehabilitation, compensation, or retraining approaches are best integrated into current AUD treatments for which there is already empirical support for efficacy, how improvements in specific cognitive domains are conceptualized mechanistically with respect to other hypothesized active elements of treatment, whether cognitive enhancement should be offered universally or only to those with some threshold level of cognitive impairment, and whether benefits of cognitive intervention are moderated by other person and environmental characteristics of the client.…”
Section: Facilitating Recovery and Relations To Treatment Outcomesmentioning
confidence: 99%
“…Mykhalovsky and Weir [38] caution against the standardization of clinical judgment and clinical care. Kennedy and Turkstra [28] further analyze a number of the limitations of relying on high levels of evidence, particularly the RCT. First, with large sample sizes, group heterogeneity may mask individual treatment benefits.…”
Section: Limitations Of the Rct In The Context Of Abi Rehabilitationmentioning
confidence: 99%
“…expertise in ABI), available time and funding and compliance, in addition to the varying cognitive and communication demands of home, work, or school [9,32,63]. While in earlier studies, severity of injury was used to equate experimental samples, it is now recognized that consideration of the cognitive, communication and behavioural profiles is necessary when comparing subjects [28,32]. To rely solely on a diagnosis of moderate-severe ABI is erroneous, as there can be many different presentations and needs that accompany this complex designation [66].…”
Section: Limitations Of the Rct In The Context Of Abi Rehabilitationmentioning
confidence: 99%